2021
DOI: 10.3390/vaccines9101189
|View full text |Cite
|
Sign up to set email alerts
|

Novel Recombinant Newcastle Disease Virus-Based In Ovo Vaccines Bypass Maternal Immunity to Provide Full Protection from Early Virulent Challenge

Abstract: Newcastle disease (ND) is one of the most economically important poultry diseases. Despite intensive efforts with current vaccination programs, this disease still occurs worldwide, causing significant mortality even in vaccinated flocks. This has been partially attributed to a gap in immunity during the post-hatch period due to the presence of maternal antibodies that negatively impact the replication of the commonly used live vaccines. In ovo vaccines have multiple advantages and present an opportunity to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…These findings suggest that IFN-γ may act as an antiviral factor and has no augmenting effect on virus immunogenicity. Interestingly, two independent studies revealed a robust function of an antisense IL-4 gene in regulating NDV immunogenicity [ 111 , 112 ]. Collectively, the data from these two works indicated that in ovo immunization with attenuated NDVs carrying an antisense IL-4 gene induced an early antibody response and high protection in commercial chicken eggs with high MDA titres.…”
Section: Experimental Nd Vaccinesmentioning
confidence: 99%
“…These findings suggest that IFN-γ may act as an antiviral factor and has no augmenting effect on virus immunogenicity. Interestingly, two independent studies revealed a robust function of an antisense IL-4 gene in regulating NDV immunogenicity [ 111 , 112 ]. Collectively, the data from these two works indicated that in ovo immunization with attenuated NDVs carrying an antisense IL-4 gene induced an early antibody response and high protection in commercial chicken eggs with high MDA titres.…”
Section: Experimental Nd Vaccinesmentioning
confidence: 99%
“…According to reports, there have been at least four major outbreaks of ND around the world, which have caused great harm to international trade, and each epidemic had its specific genotype ( 2 ). Despite the wide use of ND vaccination programs in the poultry industry, different wild strains of the immunized flock are still isolated ( 3 ). Simultaneously, the emergence of atypical clinical symptoms and new strains has posed many difficulties in diagnosis, prevention, and control of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the modified NDV expressed the hemagglutinin-neuraminidase (HN) and fusion (F) genes from a different avian paramyxovirus, such as avian paramyxovirus type 8 (Steglich et al 2013) or avian paramyxovirus type 2 (Kim, Paldurai andSamal 2017, Liu et al 2018) can overcome NDV-specific MDAs interference. In addition, recombinant NDV-vectored experimental vaccine containing an antisense sequence of avian interleukin 4 (IL4R) and their backbones is able to overcome MDAs interference by administering in ovo at 18-day-old commercial eggs (Dimitrov et al 2021). During the last few years, replicationdefective human adenoviruses serotype-5 (hAdVs-5) has emerged as an attractive vector for the development of vaccines to overcome MDAs interference in poultry.…”
Section: Live Vector Vaccinementioning
confidence: 99%